Double Jeopardy: The Cardiovascular Exposome of Athletes in Heat and Pollution: a mini review - Korzeniowska, Anna; Szafraniec, Artur; Chmiela, Mateusz (Quality in Sport, 2026)
Background: Ambient heat and air pollution form a "hostile environment" that triggers a severe cardiovascular bottleneck, forcing a direct conflict between thermoregulatory skin blood flow and working muscles while inhaled pollutants drive systemic inflammation. Aim: To synthesize the compound cardiovascular risks of this dual-stressor exposome and establish a practical clinical framework to safeguard athletes. Material and methods: A narrative synthesis of recent literature was performed, evaluating physiological, multi-omics, and epidemiological data on the cardiorespiratory impacts of exercising under thermal and pollutant stress. Results: Heat and pollution interact synergistically to degrade athletic output. Thermal vasodilation accelerates the translocation of ultrafine particles into the bloodstream, compounding myocardial oxygen supply-demand mismatches, decreasing heart rate variability (HRV), and inducing a pro-thrombotic state. Acclimation protocols might become a crucial strategy in hostile training. Practical mitigation shifts clinical management toward continuous tracking via multi-sensor wearables, diurnal planning, and spatial separation from major traffic zones. Conclusions: The compound strain of heat and pollution elevates cardiac risk and shortens time to exhaustion. Clinicians must transition to continuous longitudinal monitoring, mandate acclimation protocols, and engage in environmental health advocacy.